α-Csp3–H Bond Functionalization of Simple Ethers in Radical Reactions - Feng, Yanping; Ye, Xiajuan; Huang, Dayun; Guo, Sheng-rong (Synthesis, 2021)
The direct α-Csp3–H functionalization of simple ethers is a vital strategy among radical reactions. This review discusses their applications according to the starting materials: (1) reactions with alkenes or alkynes; (2) reactions with other unsaturated compounds; and (3) reactions with nucleophilic partners. Mechanisms like radical addition, C–H activation, elimination, metal-catalyzed coupling, cyclization, oxidation, and rearrangement will be analyzed herein.1 Introduction2 Reactions with Alkenes or Alkynes3 Reactions with Other Unsaturated Compounds4 Reactions with Nucleophilic Partners5 Oxidation of Ethers6 Conclusions
Keywords: ether; radical; Csp3–H bond functionalization